Antioxidant Stability of Moringa Leaves Extract Powders Obtained by Cocrystallization, Vacuum Drying, and Plating - Bambang Nurhadi; Fatsyarien Citra Angiputri; Robi Andoyo; Riksfardini Annisa Ermawar; Rudy Adi Saputra (Journal of Food Quality)
Cocrystallization, vacuum drying, and plating are three potential applications to preserve the antioxidant activity of moringa leaves. Moringa leaves extract was incorporated with sucrose at the same concentration (7 : 100, solid : solid) for all applications and stored for 30 days. This study aims to examine the effects of each application on the antioxidant stability of moringa leaves extract powders. Morphological properties by SEM showed that cocrystallized powders exhibited porous, agglomerated crystals, vacuum dried powders exhibited agglomerated crystals, and plated powders exhibited layered crystals. Based on XRD and hygroscopicity results, cocrystallization produced powders with the highest crystallinity, i.e., 69.11%, and the lowest hygroscopicity, i.e., 0.26 × 10−4 ± 0.02 × 10−4 g H2O/g solid/minute due to the slow water intake of the crystalline structure. Powders with the strongest initial antioxidant activity were obtained from cocrystallization, i.e., 3647.96 ± 20.29 ppm and followed by vacuum drying, i.e., 4378.51 ± 26.29 ppm. The least antioxidant activity was obtained from plating, i.e., 4733.46 ± 31.91 ppm. During 30 days of storage, powders obtained by cocrystallization maintained the most stable antioxidant activity (91.81–91.12%). The results indicated that the high temperature used in the process was likely to impact crystalline structure through the pore formation, which entrapped bioactive compounds and resulted in strong antioxidant activity. While, vacuum drying resulted in powders with a lower but increased antioxidant activity (84.06%–86.43%). In contrast to the other two applications, plating resulted in a decreased antioxidant activity (83.77–82.25%). This study suggests that application of cocrystallization produced moringa leaves extract powders with the strongest and most stable antioxidant activity during storage. Preserving the antioxidant stability of plant extract has been one of the major drives in the development of food encapsulation technology. Cocrystallization and vacuum drying are two relatively novel, less common techniques offering a simpler and more cost-effective method, but their effect on the antioxidant stability of moringa leaves extract has not yet been studied. This study discloses the effects of cocrystallization, vacuum drying, and plating (alternative extract incorporation method) on the antioxidant stability of moringa leaves extract powders. The results indicated that the three methods produced powders with high crystallinity and stable antioxidant stability during storage. Among the three methods, cocrystallization was the method that resulted in powders with the strongest and most stable antioxidant activity.